"The assurance of things hoped for, the conviction of things not seen": racial differences in the effects of changes in religiosity and hope in later life. Issue 2 (3rd April 2023) - Upenieks, Laura
ABSTRACT: Religious or spiritual approaches to life that promise human fulfillment requires an understanding of hope, defined as feelings of confidence that things will turn out well in the future. Drawing on longitudinal data from the 2001–2004 Religion, Aging, and Health Survey, this study sought to assess how changes in two aspects of religiosity, one public (religious attendance) and one private (beliefs in God-mediated control) affect hope over time, and whether there were racial differences in these relationships. Results from lagged dependent variable models showed that stable high and increasing religious attendance and God-mediated control beliefs over time were associated with greater hope, with the latter association stronger for Black older adults. We discuss our findings by situating hope as a resource that can aid older adults in overcoming setbacks and remaining committed to their goals.